Case Series: Acute Hemorrhagic Encephalomyelitis After SARS-CoV-2 Vaccination - Ancau, Mihai; Liesche-Starnecker, Friederike; Niederschweiberer, Johanna; Krieg, Sandro M.; Zimmer, Claus; Lingg, Charlotte; Kumpfmüller, Daniela; Ikenberg, Benno; Ploner, Markus; Hemmer, Bernhard; Wunderlich, Silke; Mühlau, Mark; et al. (Frontiers in Neurology, 2022)
We present three cases fulfilling diagnostic criteria of hemorrhagic variants of acute disseminated encephalomyelitis (acute hemorrhagic encephalomyelitis, AHEM) occurring within 9 days after the first shot of ChAdOx1 nCoV-19. AHEM was diagnosed using magnetic resonance imaging, cerebrospinal fluid analysis and brain biopsy in one case. The close temporal association with the vaccination, the immune-related nature of the disease as well as the lack of other canonical precipitating factors suggested that AHEM was a vaccine-related adverse effect. We believe that AHEM might reflect a novel COVID-19 vaccine-related adverse event for which physicians should be vigilant and sensitized.